2009
DOI: 10.1021/jf901839h
|View full text |Cite
|
Sign up to set email alerts
|

California Hass Avocado: Profiling of Carotenoids, Tocopherol, Fatty Acid, and Fat Content during Maturation and from Different Growing Areas

Abstract: The California Hass avocado (Persea Americana) is an example of a domesticated berry fruit that matures on the tree during its growing season but ripens only after being harvested. Avocados are typically harvested multiple times during the growing season in California. Previous research has demonstrated potential health benefits of avocados and extracts of avocado against inflammation and cancer cell growth, but seasonal variations in the phytochemical profile of the fruits being studied may affect the results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
96
1
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(109 citation statements)
references
References 11 publications
7
96
1
5
Order By: Relevance
“…are highly nutritious being rich in oleic, palmitic, linoleic and palmitoleic acids; vitamin A, B, C, E and K; and the minerals, potassium, phosphorus, magnesium and iron (Lu et al, 2009;Yahia, 2010). Anthracnose disease, caused by Colletotrichum gloeosporioides Penz.…”
Section: Introductionmentioning
confidence: 99%
“…are highly nutritious being rich in oleic, palmitic, linoleic and palmitoleic acids; vitamin A, B, C, E and K; and the minerals, potassium, phosphorus, magnesium and iron (Lu et al, 2009;Yahia, 2010). Anthracnose disease, caused by Colletotrichum gloeosporioides Penz.…”
Section: Introductionmentioning
confidence: 99%
“…The strip was placed inside UV-Vis cuvette in such that the formulation touches transparent side of cuvette. It was allowed to equilibrate for 15 mins to ensure levelling of the formulation between transpore tape and wall of the cuvette [18][19][20][21][22] .…”
Section: Spf Determination Transmission Spectrum Transpore Tape Methodsmentioning
confidence: 99%
“…The formulated creams were inoculated on the plates of Muller Hinton agar media by streak plate method and a control was prepared by omitting the cream 18 . The plates were placed in to the incubator and are incubated at 37 0 C for 24 hours.…”
Section: Microbiological Studies For the Herbal Creamsmentioning
confidence: 99%
“…The edible portion of the fruit is high in lipid, which varies from 3% to 30% of its fresh weight and it is also rich in oleic, palmitic, linoleic, and palmitoleic acids, as well as stearic acid in trace amounts. (19) The fatty acid composition in avocado mesocarp is as follows: oleic acid (86 mg g -1 oil), palmitic acid (32 mg g -1 oil), linolenic acid (19 mg g -1 oil) and palmitoleic acid (14 mg g -1 oil). (19) Ozdemir and Topuz (20) indicated that in "Fuerte" oleic acid is the only fatty acid that increased continuously during the season and during ripening at 20 °C for 1 week with percentages ranging from 65.5 to 71.21% while palmitic acid decreased from 18.5 to 16.0% during maturation on the tree and from 16.0 to 14.5% during ripening at 20 °C for 1 week.…”
mentioning
confidence: 99%
“…(19) The fatty acid composition in avocado mesocarp is as follows: oleic acid (86 mg g -1 oil), palmitic acid (32 mg g -1 oil), linolenic acid (19 mg g -1 oil) and palmitoleic acid (14 mg g -1 oil). (19) Ozdemir and Topuz (20) indicated that in "Fuerte" oleic acid is the only fatty acid that increased continuously during the season and during ripening at 20 °C for 1 week with percentages ranging from 65.5 to 71.21% while palmitic acid decreased from 18.5 to 16.0% during maturation on the tree and from 16.0 to 14.5% during ripening at 20 °C for 1 week. Similarly, linolenic acid showed a regular decrease as the season progressed from 4.54 to 2% and from 3.0 to 1.4% in ripening at 20 °C for 1 week.…”
mentioning
confidence: 99%